Mesostructure, contemporary training model of the Cuban boxing school - Juan Hernández Sierra; Giraldo Machuat Santana; Yusimil Ramos Quian (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
The present work aims to convey the experiences on the development and application of a meso-structure of 3-4 microcycles that allowed maintaining a long state of the sport form (5-6 months) on a scientific-technical and methodological basis in the planning of the Sports training of the national boxing team, who participated in the 4th World Boxing Series (WSB). The investigated sample consisted of 21 boxers, representing 58%, of a population made up of 36 athletes / students belonging to the National School of Boxing. The importance of the research is that it exposes the use of new planning concepts and the current modifications in the training structure, as well as the contribution of science to the adaptation of training loads, which allows to obtain positive results during a long period of time. state of the sport form, factors on which it is necessary to reflect for an effective planning of modern sports training.